Influence of inhaled nitric oxide on bronchopulmonary dysplasia in preterm infants with PPHN or HRF at birth: a propensity score matched study - Huang, Xue-rong; Wang, Lian; Liang, Guo-bao; Huang, Sheng-qian; Feng, Bao-ying; Zhu, Lu; Fan, Xu-fang; Yao, Mu-lin; Zhang, Jing; Wang, Meng-jiao; Zheng, Zhi; Zhu, Yao; et al. (Frontiers in Pharmacology, 2024)
Background: Bronchopulmonary Dysplasia (BPD) is a chronic lung disease affecting preterm infants, with limited prevention and treatment options. Inhaled Nitric Oxide (iNO) is sometimes used to treat Persistent Pulmonary Hypertension of the Newborn (PPHN) and Hypoxemic Respiratory Failure (HRF), and its impact on BPD development remains debated.Objective:To assess whether iNO-related factors are potential contributors to the development of BPD Grade Ⅱ-Ⅲ in very premature infants(VPI) diagnosed with PPHN or HRF at birth using Propensity Score Matching (PSM).We conducted a retrospective cohort study of infants born at 22-32 weeks gestation with PPHN or HRF, treated with iNO for over three hours. PSM matched groups by gestational age, birth weight, and gender etc. Multivariate logistic regression evaluated the association between iNO treatment and BPD outcomes to identify influencing factors, while Restricted Cubic Spline (RCS) and mediation analysis examined iNO dose effects and potential mediators like mechanical ventilation time and oxygenation index(OI).Results:A higher initial iNO dose was significantly associated with a reduced risk of BPD Grade Ⅱ-Ⅲ (adjusted OR = 0.68, 95% CI: 0.52-0.89, P < 0.01). Additionally, administration of iNO within the first 7 days of life was identified as an important influencing factor No significant mediation effects were observed for factors such as mechanical ventilation time and OI..A higher initial iNO dose within the first 7 days was associated with a reduced risk of BPD Grade Ⅱ-Ⅲ in VPI with PPHN or HRF.